2000
DOI: 10.1021/om000125c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of 1-Aza-allyl Complexes with Al−Al, Ga−Ga, and In−In Bonds

Abstract: The synthesis of new compounds containing Al-Al, Ga-Ga, and In-In bonds, the 1-azaallyl ligand R (R ) [(Me 3 Si) 2 C(Ph)C(Me 3 Si)N]), and halide substituents is described. The gallium(III) compound RGaCl 2 (1) was prepared by reaction of GaCl 3 with RLi‚THF. The reduction of a mixture of RAlI 2 and RAlClI with potassium afforded [RIAl-AlClR] (2).[RGaCl] 2 (3) was synthesized by the reduction of RGaCl 2 with sodium/potassium alloy, while [RInBr] 2 (4) was prepared by reaction of RLi‚THF with indium(I) bromide.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…The OH group in 3 occupies the position of the more strongly bound Cl in 2a and the bromine that of the less strongly bound atom. In the compounds LL′GaCl 2 , Ga-N bonds are usually longer than Ga-C bonds (for an exception see [22]). The Ga-N [2.047(5) Å ] and Ga-C bond lengths [2.008(5) Å ] in 3 are within the reported ranges [Ga-N 2.013(2)-2.092(5) Å and Ga-C 1.936(6)-2.013(7) Å [15,16,23]] and close to the values [Ga-N 2.057(4), Ga-C 2.000(4) Å ] found for the compound GaCl 2 C(SiMe 3 ) 2 (SiMe 2 NMe 2 ) (5c) [13].…”
Section: Resultsmentioning
confidence: 99%
“…The OH group in 3 occupies the position of the more strongly bound Cl in 2a and the bromine that of the less strongly bound atom. In the compounds LL′GaCl 2 , Ga-N bonds are usually longer than Ga-C bonds (for an exception see [22]). The Ga-N [2.047(5) Å ] and Ga-C bond lengths [2.008(5) Å ] in 3 are within the reported ranges [Ga-N 2.013(2)-2.092(5) Å and Ga-C 1.936(6)-2.013(7) Å [15,16,23]] and close to the values [Ga-N 2.057(4), Ga-C 2.000(4) Å ] found for the compound GaCl 2 C(SiMe 3 ) 2 (SiMe 2 NMe 2 ) (5c) [13].…”
Section: Resultsmentioning
confidence: 99%
“…Metal iodides are often employed as precursors to low valent group 4 [8][9][10] and group 13 [11][12][13] complexes since reductions of metal iodides often produce higher product yields than reductions of analogous bromides and chlorides. For example, Roesky and coworkers found that reduction of [Cp * AlX 2 ] 2 with Na/K to give [Cp * Al] 4 proceeded in greatest yield when X = I [14].…”
Section: Synthesis Of Scandium(iii) Precursorsmentioning
confidence: 99%
“…1 H NMR (methylene chloride-d 2 ): d 1.88 (s, 15H, C 5 Me 5 ), 2.56 (s, 6H, Me 2 -bpy), 7.35 (s, 0.75H, 1/8C 6 H 6 ), 7.46 (d, 2H, J = 5.6 Hz, bpy), 7.97 (s, 2H, bpy), 9.54 (d, 2H, J = 5.6 Hz, bpy). 13 …”
Section: Synthesis Of [Cp * Sci 2 (L-dmpe)] 2 (2)mentioning
confidence: 99%
“…Elemental analyses were performed by the Analytisches Chemisches Laboratorium des Instituts fu È r Anorganische Chemie, Go È ttingen. (1) 115.87 (7) Mg (1) (2) 2.0624 (16) Mg (1) 13 (dipp)NacNacMg(l-H) 3 …”
Section: Experimental Partmentioning
confidence: 99%
“…The first b-diketoiminate derivatives of magnesium were synthesized by Kuhn et al in 1987 [7]. Gibson Monomeric (dipp)NacNacMgI can function as an interesting precursor for the preparation of a low valent metal complex by reduction of the iodine complex with alkaline metals [13].…”
Section: Introductionmentioning
confidence: 99%